Roma music under the microscope of contemporary musicians: Introduction - Berkyová, Renata (Romano džaniben, 2022)
Introduction to the section on current views on Romani music. The contribution was inspired by a debate broadcasted on social media on the International Day of the Roma which focused on Romani music, the interest in it among the non-Romani society, folklore trends and recent shifts. Two Romani musicians and guests of the debate were approached to write on the topic: Vojtěch Lavička and Jan Dužda, who wrote his text in Romani. The final part presents the results of a short survey that asked: What is your favourite Romani song lyric and why?